Advanced DC zonal marine power system protection. Issue 2 (1st February 2014) - Jia, Ke; Christopher, Edward; Thomas, David; Sumner, Mark; Bi, Tianshu
Abstract : A new active impedance estimation based protection strategy which is suitable for utilisation in a DC zonal marine power distribution system is presented. This method uses two triangular current 'spikes' injections for system impedance estimation and protection when faults are detected. By comparing the estimated impedance with the pre‐calibrated value, the fault location can be predicted and fault can be isolated without requiring communication between two injection units. Using co‐ordinated double injections and line current measurement (directional fault detection), faults in the system with same impedance and different fault positions can be distinguished, located and isolated. The proposed method is validated using experimental test results derived from a 30 kW, 400 V, twin bus DC marine power system demonstrator. The experimental tests were applied to both faults during normal operation and faults that occur during system restoration.